Effect of high nutrient-density diets on starter pig performance - B C Thaler; G L Allee; Jim L Nelssen (Kansas Agricultural Experiment Station Research Reports, 1985)
Two experiments and an on-farm trial were conducted to compare the performance of weanling pigs fed a high nutrient-density diet (HNDD) to the performance of pigs fed standard corn-soybean meal (C-SBM) diets. A total of 358 crossbred weanling pigs (approximately 21 days of age) were allotted to experimental treatments based on initial weight and ancestry. Average initial pen weights ranged from 6.5 to 21.9 lb for the three trials. Dietary treatments consisted of feeding HNDD for 1 or 2 weeks followed by either 20% whey diets and/or 1.25% lysine C-SBM diets, a 20% whey diet for 2 weeks followed by a 1.25% lysine corn-S8M diet, a 20% whey diet for five weeks, or a 1.25% lysine C-SBM diet for 5 weeks.; Swine Day, Manhattan, KS, November 21, 1985
Keywords: Swine day; 1985; Kansas Agricultural Experiment Station contribution; no. 86-145-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 486; Swine; High nutrient-density diets; Pig performance